Avocado Oil Supplementation Modifies Cardiovascular Risk Profile Markers in a Rat Model of Sucrose-Induced Metabolic Changes - Octavio, Carvajal-Zarrabal; Cirilo Nolasco, Nolasco-Hipólito; M. Guadalupe, Aguilar-Uscanga; Guadalupe, Melo-Santiesteban; Hayward-Jones, Patricia M.; Barradas-Dermitz, Dulce M. (Hindawi Publishing Corporation, 2014)
The purpose of this study was to evaluate the effects of avocado oil administration on biochemical markers of cardiovascular risk profile in rats with metabolic changes induced by sucrose ingestion. Twenty-five rats were divided into five groups: a control group (CG; basic diet), a sick group (MC; basic diet plus 30% sucrose solution), and three other groups (MCao, MCac, and MCas; basic diet plus 30% sucrose solution plus olive oil and avocado oil extracted by centrifugation or using solvent, resp.). Glucose, total cholesterol, triglycerides, phospholipids, low- and high-density lipoproteins (LDL, HDL), very low-density lipoprotein (VLDL), lactic dehydrogenase, creatine kinase, and high sensitivity C-reactive protein concentration were analyzed. Avocado oil reduces TG, VLDL, and LDL levels, in the LDL case significantly so, without affecting HDL levels. An effect was exhibited by avocado oil similar to olive oil, with no significant difference between avocado oil extracted either by centrifugation or solvent in myocardial injury biochemical indicators.Avocado oil decreased hs-CRP levels, indicating that inflammatory processes were partially reversed. These findings suggested that avocado oil supplementation has a positive health outcome because it reduces inflammatory events and produces positive changes in the biochemical indicators studied, related to the development of metabolic syndrome.